“Fighting for the Floor”: Overlap as A Rhetorical Strategy of Power and Urgency in Geopolitical Debate - Intan Permata Sari; Otong Setiawan Djuharie; Erfan Muhamad Fauzi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
Overlap in geopolitical debates, particularly the Israel-Palestine conflict, remains underexplored in conversation analysis research. This study addresses that gap through the case of “Can Israel Make Peace with Hamas?”, a debate on the Open to Debate YouTube channel marked by confrontation between speakers holding opposing positions. Using Jefferson's (1983)overlap-onset framework and Schegloff's (2000) resolution mechanisms, this qualitative case study analyzes 133 turns of talk produced by two debaters, Cenk Uygur and Mosab Hassan Yousef, and moderator John Donvan, to identify overlap types and how speakers manage simultaneous talk. The findings reveal 24 instances of overlap onset (18.04%), with recognitional onset as the most dominant type, accounting for 16 instances (12.03%), followed by transitional onset with 8 instances (6.01%), and no progressional onset observed. As for resolution, 22 instances were identified (16.54%), with withdrawal as the most frequent mechanism, accounting for 10 instances (7.52%), followed by persistence with 8 instances (6.02%) and acoustic upgrade with 4 instances (3.01%). These findings demonstrate that overlap functioned as a deliberate rhetorical strategy reflecting power, urgency, and argumentative control in this case, not as a generalizable claim about geopolitical debate.